Prairie up : an introduction to natural garden design - Vogt, Benjamin (3 Fields Books, an imprint of the University of Illinois Press, 2023)
"Landscaping with native plants has encouraged Midwesterners to embark on a profound scientific, ecological, and emotional partnership with nature. Benjamin Vogt shares his years of expertise with prairie plants in a full-color guide aimed at gardeners, homeowners, and landscape designers. Step-by-step blueprints point readers to plant groupings that not only attract pollinators and please the eye but minimize maintenance and ensure years of healthy growth. In addition, Vogt gives proven tips on everything from invasive plants to essential tools to working with skeptical homeowner associations. Outside experts also provide inspiration while a section of additional resources makes the book an invaluable reference. Easy to use and illustrated with over 150 color photos, Prairie Up is a practical guide to reviving diversity and wildness in our communities"--